Perancangan Motif Batik dengan Sumber Ide Pohon Keben melalui Teknik Batik Cap - Gayuh Murdianto (Hastagina : Jurnal Kriya Seni, 2022)
Gayuh Murdianto. C0914018. 2021. This design is inspired by coastal batik in Cilacap which is more often called Maos batik. It has a blend of inland and coastal colors because this area is a meeting place between the culture of the Inland Palace and the Coastal area. Therefore it has an attractive dark and bright color. Generally, the patterns are of plants and animals found living in the area. One of the existing plants is the keben (Barringtonia asiatica) tree which is said to not only grow on the coast but also grows in the Yogyakarta Palace. It is interesting to be appointed as a motif designing project into Cilacap coastal batik through stamped batik techniques. The designing method uses Collin Clipson's theory whose creative process aims to meet human needs by considering several important aspects including aspects of function, aesthetics, materials and processes. The technique uses the stamp technique with the aim that the product being made can meet market demand in large quantities. Judging from the cost of production, this batik is expected to be affordable by the community. Steps from problem identification to marketing distribution are clearly considered. The result of this project is stamped batik with the main motifs taken from the keben tree, ranging from flowers, fruit, leaves and stems in a stylized style to produce a harmonious pattern with Cilacap coastal batik through the stamp batik technique.